Emerging adults' cultural values, prosocial behaviors, and mental health in 14 countries during the COVID-19 pandemic. (July 2022) - Padilla-Walker, Laura M.; Van der Graaff, Jolien; Workman, Katey; Carlo, Gustavo; Branje, Susan; Carrizales, Alexia; Gerbino, Maria; Gülseven, Zehra; Hawk, Skyler T.; Luengo Kanacri, Paula; Mesurado, Belén; Samper-García, Paula; et al.
Evidence suggests an impact of the COVID-19 pandemic on mental health, particularly among emerging adults. However, theories on altruism born of suffering or adversarial growth suggest that we might also see prosocial behavior as a function of the pandemic, which may protect against mental health challenges. Because cultural values are central in determining prosocial behavior, the current study explored how cultural values were differentially associated with adaptive prosocial behaviors that might protect against mental health challenges. Participants for the current study included 5, 682 young people aged 18–25 years from 14 different countries around the world (68% female, 62% college students). Path analyses suggested that there were few differences in patterns as a function of culture, but revealed that horizontal individualism and horizontal and vertical collectivism were indirectly associated with lower levels of depression via prosocial behavior toward family members. Discussion focuses on the importance of coping by strengthening family relationships via prosocial behavior during the pandemic.